IMPROVING THE CAPACITY OF MSMES THROUGH OPTIMIZING THE IMPLEMENTATION OF INSTITUTIONAL MANAGEMENT TOWARDS GLOBAL COMPETITIVENESS OF MSMES - Anggia Sari Lubis; Yuni Shara; Maria Kristina Situmorang; Putri Yunizars (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
The aim of this paper is to look at increasing the capacity of MSMEs through optimizing the implementation of institutional management towards global competitiveness of MSMEs. Globalization makes competition increasingly fierce among business people throughout the world. The influence of globalization has an impact on domestic entrepreneurs, this condition makes the products they sell compete with foreign products entering the country. Globalization has positive and negative impacts, entrepreneurs are able to adapt in the era of globalization by maximizing its positive impacts. In order to compete with business products from abroad, MSME players must increase their capacity and capabilities. MSMEs play an important role in improving the performance of the Indonesian economy. Increasing the capacity and capability of MSMEs is important for the Indonesian Government in maintaining the existence and increasing the scale of MSME businesses. In order for MSMEs to advance in class, it is hoped that there will be good cooperation between the government, MSME owners and related stakeholders. By increasing the capability and capacity of MSMEs in Indonesia, there is a big possibility that MSME products will be successfully exported. Exports of MSME products will encourage an increase in the scale of MSME businesses which will of course increase income and employment. One of the factors that makes MSMEs successful in moving up a class is the existence of a well-defined organizational structure in their management. Apart from supporting the efficiency and effectiveness of achieving MSME goals, this structure also clarifies job descriptions. Then, to increase the professionalism of business management, institutional management is the implementation of management functions consisting of planning, organizing, directing and controlling in all areas of management. These areas include human resource management, financial management, operational and production management, and finally financial management.